Prognostic factors for gemcitabine-refractory patients with advanced pancreatic cancer: a retrospective analysis of a multicentre study (Anatolian Society of Medical Oncology) - İnal, Ali; Kos, F. Tuba; Algın, Efnan; Yıldız, Ramazan; Berk, Veli; Unek, İlkay T.; Colak, Dilsen; Dane, Faysal; Geredeli, Caglayan; Isikdogan, Abdurrahman (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Systemic chemotherapy for patients with pancreatic cancer has limited impact on overall survival (OS). Patients eligible for chemotherapy should be selected carefully. The aim of the study was to search for prognostic factors for survival in patients with gemcitabine (Gem)-refractory or with gemcitabine and cisplatin (GemCis)-refractory advanced pancreatic cancer. Material and methods: We retrospectively evaluated patients with Gem- or GemCis-refractory advanced pancreatic cancer. Sixteen potential prognostic variables were chosen for analysis in this study. Univariate and multivariate analyses were conducted to identify prognostic factors associated with survival. Univariate and multivariate statistical methods were used to determine prognostic factors. Results : Multivariate analysis included the four prognostic significance factors in univariate analysis. Multivariate analysis showed that liver metastasis and second-line chemotherapy were considered independent prognostic factors for survival. Conclusions : Liver metastasis and second-line chemotherapy were identified as important prognostic factors in advanced pancreatic cancer patients refractory to treatment with Gem or GemCis. This prognostic factors may also facilitate pretreatment prediction of survival and can be used for selecting patients for treatment.